Parasites of orangutans (primates: ponginae): An overview. Issue 6 (27th March 2017) - Nurcahyo, Wisnu; Konstanzová, Veronika; Foitová, Ivona
Abstract : Wild orangutan populations exist in an increasingly fragile state. As numbers continue to decline and populations became fragmented, the overall health of remaining individuals becomes increasingly at risk. Parasitic infections can have a serious impact on the health of wild orangutans, and can be fatal. It has been reported that rehabilitated individuals demonstrate a higher prevalence of parasitic diseases, and it is possible that they may spread these infections to wild orangutans upon reintroduction. In order to ensure the success of reintroduction and conservation efforts, it is crucial to understand the potential risks by fully understanding what parasites they have been reported to be infected with. Using this knowledge, future conservation strategies can be adapted to minimize the risk and prevalence of parasite transmission in the remaining orangutan populations. There is still limited information available on orangutan parasites, with several still not identified to the species level. Based on comprehensive literature review, we found 51 parasite taxa known to infect wild, semi‐wild, and captive orangutans, including newly reported species. Here, we summarize methods used to identify parasites and draw conclusions relative to their reported prevalence. We also recommend fecal sample preservation and analytical methods to obtain best result in the future.